# Solve, showing details: y' 1 = y 1 + 4y 2 - t 2 + 6t y' 2 = y 1 + y 2 - t 2 + t - 1 y 1 (0) = 2, y 2 (0) = -1

Chapter 4, PROBLEM SET 4.6 #12

Solve, showing details:

y'_{1} = y_{1} + 4y_{2} - t^{2} + 6t

y'_{2} = y_{1} + y_{2} - t^{2} + t - 1

y_{1}(0) = 2, y_{2}(0) = -1

## This problem has been solved!

Do you need an answer to a question different from the above? Ask your question!

**Related Book For**

P R O B L E M S E T 4 . 3:

- PROBLEMSET4.3-1
- PROBLEMSET4.3-2
- PROBLEMSET4.3-3
- PROBLEMSET4.3-4
- PROBLEMSET4.3-5
- PROBLEMSET4.3-6
- PROBLEMSET4.3-7
- PROBLEMSET4.3-8
- PROBLEMSET4.3-9
- PROBLEMSET4.3-10
- PROBLEMSET4.3-11
- PROBLEMSET4.3-12
- PROBLEMSET4.3-13
- PROBLEMSET4.3-14
- PROBLEMSET4.3-15
- PROBLEMSET4.3-16
- PROBLEMSET4.3-17
- PROBLEMSET4.3-18
- PROBLEMSET4.3-19
- PROBLEMSET4.3-20

P R O B L E M S E T 4 . 4:

P R O B L E M S E T 4 . 5:

PROBLEM SET 4.6: